2013
DOI: 10.1371/journal.pone.0083703
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Characterization of Sulfated Carbohydrate-Binding Protein from Lactobacillus reuteri

Abstract: We previously purified a putative sulfated-galactosylceramide (sulfatide)-binding protein with a molecular weight of 47 kDa from the cell surface of Lactobacillus reuteri JCM1081. The aim of this study was to identify the 47-kDa protein, examine its binding to sulfated glycolipids and mucins, and evaluate its role in bacterial adhesion to mucosal surfaces. By cloning and sequencing analysis, the 47-kDa protein was identified as elongation factor-Tu (EF-Tu). Adhesion properties were examined using 6×Histidine-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 38 publications
(63 reference statements)
2
46
0
2
Order By: Relevance
“…Similar to our findings, L-asparaginase II and EF-Tu have been reported to be immunogenic in other pathogenic bacteria (49,(54)(55)(56)(57)(58)(59). In addition, other studies have described the presence of EF-Tu in E. coli OM or OMP extracts (32,(60)(61)(62)(63)(64), as well as the interaction of EF-Tu with fibronectin (65), indicating the participation of EF-Tu in adhesion to human intestinal cells and mucin (66)(67)(68). It is also possible that EF-Tu belongs to the group of moonlighting proteins (69,70), which can be found in various locations within the bacterial cell and fulfill specific functions that vary by location.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, L-asparaginase II and EF-Tu have been reported to be immunogenic in other pathogenic bacteria (49,(54)(55)(56)(57)(58)(59). In addition, other studies have described the presence of EF-Tu in E. coli OM or OMP extracts (32,(60)(61)(62)(63)(64), as well as the interaction of EF-Tu with fibronectin (65), indicating the participation of EF-Tu in adhesion to human intestinal cells and mucin (66)(67)(68). It is also possible that EF-Tu belongs to the group of moonlighting proteins (69,70), which can be found in various locations within the bacterial cell and fulfill specific functions that vary by location.…”
Section: Discussionsupporting
confidence: 90%
“…Porcine mucins have been used as a model for testing the in vitro adhesion capacity of probiotic bacteria for many years. 15,[25][26][27][28] Mucus layers are a heterogeneous mixture of antibacterial proteins, IgA, nucleic acids, and undigested materials; 29) however, little is known Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study showed that elongation factor Tu (EF-Tu), localized on the cell surface of L. reuteri JCM1081, bound to sulfated carbohydrates of mucins. 15) The binding characteristics of EF-Tu in bifidobacteria to sulfated carbohydrates of mucins are currently under further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations